Microarchitecture-level leakage reduction with data retention. - Weiping Liao (IEEE Transactions on VLSI systems)
In this paper, we study microarchitecture-level leakage energy reduction by power gating. We consider the virtual power/ground rails clamp (VRC) and multithreshold CMOS (MTCMOS) techniques and apply VRC to memory-based units for data retention and MTCMOS to the other units. We propose a systematic methodology for leakage reduction at the microarchitecture level, in which profiling of idle period distribution and ideal power gating analysis are used to select a target component for realistic power gating. We show that the ideal leakage energy reduction can be up to 30% of the total energy for the modern high-performance very long instruction word processors we study and that the secondary level (L2) cache contributes most to the reduction. We further improve the existing adaptive cache decay method for leakage reduction by using VRC for data retention and name it VRC decay . Applied to L2 cache, the VRC decay, on average, increases performance by 5.6% and reduces system energy by 24.1%, compared to the adaptive cache decay without data retention.